Complex Decisions in the Management of Congenital Pseudarthrosis of the Tibia : Panel Discussion - Laine, Jennifer; Choi, In-Ho; Dahl, Mark; Herzenberg, John; Horn, Joachim; Iobst, Christopher; Johnston, Charles; Joseph, Benjamin; McClure, Philip K.; Noonan, Kenneth; Shah, Hitesh (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Congenital pseudarthrosis of the tibia, or congenital tibial dysplasia, is one of the most challenging conditions in pediatric orthopaedics. In children who present in a pre-fracture state, the initial goal is fracture prevention. Once the tibia has fractured, the goals of treatment pivot to achieving – and maintaining – union. Treatment approaches are varied and may include: pseudarthrosis resection, intramedullary(IM) fixation, circular external fixation, internal fixation, vascularized fibular grafting, biologics, guided growth, or a combination of approaches. Unfortunately, the treatment of this condition is often fraught with complications and it is not unusual for a child to undergo multiple procedures. The goals of this case discussion are to highlight how experts approach these complex cases, to emphasize the key components of decision-making, to demonstrate clinical and technical pearls, and to feature the heterogeneity of this condition and its treatment.